Yellow Fever Virus modulates the expression of key proteins related to the microRNA pathway in the human hepatocarcinoma cell line HepG2 - Holanda, Gustavo Moraes (Mary Ann Liebert, 2017)
Yellow fever is a zoonotic disease caused by the yellow fever virus (YFV) and transmitted by mosquitoes of the family Culicidae. It is well known that cellular and viral microRNAs (miRNAs) are involved in modulation of viral and cellular gene expression, as well as immune response, and are considered by the scientific community as possible targets for an effective therapy against viral infections. This regulation may be involved in different levels of infection and clinical symptomatology. We used viral titration techniques, viral kinetics from 24 to 96 hours postinfection (hpi), and analyzed the expression of key proteins related to the miRNA pathway by quantitative reverse transcriptase polymerase chain reaction (qRT-PCR). The expression of Dicer was different when compared over the course of infection by the distinct YFV genotypes. Drosha expression was similar during infection by YFV genotype 1 or 2, with a decrease in their expression over time and a slight increase in 96?hpi. Ago1, Ago2, and Ago4 showed different levels of expression between the viral genotypes: for YFV genotype 1 infection, Ago1 presented a positive expression, while for YFV genotype 2, it showed a negative expression, when compared with negative controls. We conclude that YFV infection modulates the proteins involved in miRNA biogenesis, which can regulate both viral replication and cellular immune response.